Peran Kejaksaan dalam Penanggulangan Tindak Pidana Korupsi di Indonesia - Nuryono Nuryono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Corruption is still a scourge and a sore that destroys the economic joints of a country or nation. Problem formulation: 1) What is the normative basis of the authority of the District Attorney's Office in overcoming corruption; 2). What is the role of the District Attorney's Office in overcoming corruption? This research will be compiled using the normative legal research type. The data sources used are primary and secondary data. Secondary data in this study include: Primary legal materials, consisting of: Law Number 48 of 2009 concerning Judicial Power, Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia, Law Number 31 of 1999 which has been amended to Law Number 21 of 2001, Law Number 30 of 2002 concerning the Corruption Eradication Commission, Law Number 46 of 2009 concerning the Corruption Court. Research results: 1). Protection of patient rights as consumers in medical records is the existence of regulations that The normative basis for the authority of the District Attorney's Office in dealing with corruption crimes is divided into two, namely preventive handling and repressive handling. Preventive handling of corruption crimes by the prosecutor's office is an action taken within the framework before the crime or criminal act occurs, the legal basis for which is Article 30A and Article 30B letter d of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia. The main umbrella is Law Number 8 of 1981 concerning the Criminal Procedure Code, especially those stated in Article 1 number 6 letters (a) and (b) of the Criminal Procedure Code. The prosecutor as a criminal investigator also serves as a public prosecutor in handling corruption crimes. So to complete his obligations, the prosecutor must cooperate with other related parties. Cooperation with other parties is called a legal relationship, because in carrying out cooperation in a rule or law that is certain in nature. Legal relations with other parties can be individuals, legal entities and other government agencies.